Low plasma levels of B-type natriuretic peptide predict the insulin resistance and left ventricular concentric remodeling in subjects without heart diseases: the observational arita cohort study. (14th October 2021) - Okamoto, C; Hasegawa, T; Tsukamoto, O; Hitsumoto, T; Matsuoka, K; Takashima, S; Amaki, M; Kanzaki, H; Izumi, C; Ito, S; Kitakaze, M
Abstract: Introduction: Although natriuretic peptides (NPs) are established as a biomarker of heart failure (HF), NPs have been attracting attention as a mediator in the metabolic sequences recently. On the other hand, metabolic disorders including insulin resistance have been suggested to be involved in left ventricular (LV) concentric remodeling, hinting us to the unexpected relationship among NPs, insulin resistance and LV concentric remodeling. Purpose: To investigate whether the basal B-type natriuretic peptide (BNP) level is linked to insulin resistance or LV concentric remodeling in the participants independent of HF in the Japanese Arita-cho cohort study. Methods: Among 1632 subjects who participated in annual health checks from 2005 to 2008 in Arita-cho, Saga, Japan as a cohort study, we studied 675 subjects without history of cardiovascular disease with LV ejection fraction≥50% and BNP level<35pg/ml (227 men; median 62 years old). Insulin resistance was assessed by homeostatic model assessment of insulin resistance (HOMA-IR) and LV geometry including LV concentric remodeling was classified based on relative wall thickness (RWT) and LV mass index from echocardiographic findings. Results: The tertile levels of BNP were inversely associated with HOMA-IR (the 1st tertile 1.33 (0.76–1.74), the 2nd tertile 1.05 (0.72–1.59), the 3rd tertile 0.95 (0.66–1.58), p=0.005); in the logistic regression analysis, the lower BNP level was related to the prevalence of insulin resistance defined as HOMA-IR≥1.37 after full multivariate adjustment (1 SD increment of BNP: adjusted odds ratio [aOR] 0.740, 95% confidence interval 0.601–0.912, P=0.005. LV concentric remodeling (RWT >0.42 and LV mass index ≤115 g/m 2 in men and ≤95 g/m 2 in women) was observed in 170 (25%) subjects; both low BNP level and higher insulin resistance were independently linked with LV concentric remodeling after multivariate adjustment (1 SD increment of BNP: aOR 0.714, 95% CI 0.544–0.938, p=0.015, HOMA-IR≥1.37 vs. <1.37: aOR 1.694, 95% CI 1.004–2.857, p=0.048, respectively) (Figure). Conclusions: In the cohort without HF, the low BNP level was linked to insulin resistance and LV concentric remodeling independently, suggesting that the subjects with low NPs levels may cause metabolic disorders and LV morphological abnormalities. Funding Acknowledgement: Type of funding sources: None.